The Acceptance of COVID-19 Vaccine: The Projection from the First Year of COVID-19 Pandemic in Indonesia - Insani Sadarang, Rimawati Aulia; Karini, Tri Addya; Kurniati, Yessy (citeus, 2023)
This study aimed to describe the acceptance of the COVID-19 vaccine and to discover predictive factors of vaccine acceptance in Indonesia. A cross-sectional study with 164 respondents found that 70.1% would accept the vaccine. Trust in government press releases, perception of infection risk, and age were significant factors. Logistic regression showed a predictive model with 73% performance, highlighting the importance of government trust and evidence-based messaging.